Developmental evolution: insights from studies of insect segmentation. - Patel, N.H. (Science, 1994)
Rapid advances have been made in the understanding of the genetic basis of development and pattern formation in a variety of model systems. By examining the extent to which these developmental systems are conserved or altered between different organisms, insight can be gained into the evolutionary events that have generated the diversity of organisms around us. The molecular and genetic basis of early pattern formation in Drosophila melanogaster has been particularly well studied, and comparisons to other insects have revealed conservation of some aspects of development, as well as differences that may explain variations in early patterning events.